Analisis Literatur Implementasi Qardhul Hasan di BMT Syariah Indonesia melalui Lensa Akad Qard dan ‘Ariyah - Tsania Salma; Kuhasumi Agyta Hidayah; Ananda Della Putri Cahyani; Kamelia Riskia Putri; Selvi Rahmadani; Taufiq Kurniawan (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
This study aims to examine the implementation of Qardhul Hasan in Islamic Microfinance Institutions (Baitul Maal wat Tamwil – BMT) in Indonesia through the perspective of qard and ‘Ariyah contracts. The research applies a qualitative descriptive approach using a library research method. Data were collected from scholarly articles, books, and Islamic finance regulations, then analyzed to assess the alignment between fiqh al-mu‘āmalah principles and real-world practices. The findings reveal that qardhul hasan plays a vital role in community empowerment and in promoting Islamic financial inclusion. However, its implementation still faces several obstacles, including high non-performing financing rates, limited social funds, weak sharia supervision standards, and low literacy in fiqh mu‘āmalah among BMT managers. On the other hand, there are significant opportunities for development through digital transformation, human resource capacity building, optimization of social funds (ZISWAF), and the strengthening of regulations based on maqāṣid al-sharī‘ah. This study proposes an integrative model combining qard and ‘ariyah contracts as an alternative approach to enhance the social function of BMTs while maintaining financial sustainability.